Critical facilities for active participation in learning networks. (12th January 2006) - Hummel, Hans G.K.; Tattersall, Colin; Burgos, Daniel; Brouns, Francis; Kurvers, Hub; Koper, Rob
This article investigates conditions for increasing active participation in online communities. As a case study, we use three generations of facilities designed to promote learning in the area of Educational Modelling Languages. Following a description of early experience with a conventional website and with a community site offering facilities for collaboration, we describe a pilot implementation of a learning network. Preliminary participation data (both passive and active) is reported, together with lessons learned while setting up the pilot. Early experiences reveal that clear policies, usability and reward systems are of importance when facilitating a learning network. We reveal first (positive) findings with introducing such a reward mechanism in the network. Our 'lessons learned' are phrased in terms of recommendations which will be used to guide subsequent learning network implementations.